Variation in Phenolic Compounds and Antioxidant Activity of Various Organs of African Cabbage (Cleome gynandra L.) Accessions at Different Growth Stages - Maina, Sylvia; Ryu, Da Hye; Bakari, Gaymary; Misinzo, Gerald; Nho, Chu Won; Kim, Ho-Youn (MDPI, 2021)
The presence of nutritional and health-benefiting compounds has increased awareness of orphan leafy vegetables such as Cleome gynandra (CG), whose phytochemicals vary among accessions and organs during growth. This study investigated the polyphenol accumulation and antioxidant activities (AOA) of eight CG accessions from the vegetative stage to the seed set stage. Plants were separated into leaves and stem (LS), flowers, and silique organs, and extracts were analyzed for total phenolic content (TPC), total flavonoid content (TFC), rutin and astragalin content, and AOA using 2,2-diphenyl-1-picrylhydrazyl-hydrate (DPPH) and 2,2 '-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS). There were significant interaction effects of growth stages and accessions that contributed to changes in compounds content and AOA. TPC accumulated in plant generative parts, whereas flavonoids accumulated in young plant organs. HPLC profiling revealed that rutin was the most abundant compound in all organs, with flowers having the highest levels, while astragalin was only found in flowers. Silique extracts, particularly accession KF-14, recorded the highest TPC, which corresponded to the strongest radical scavenging activity in ABTS and DPPH assays and a strong linear correlation. The germplasm contained accessions with significantly different and varying levels of bioactive compounds and AOA. These findings potentiate the exploitation of CG organs such as siliques for AOA, flowers for rutin and astragalin, and young shoots for flavonoids. Moreover, the significant accumulation of the compounds in particular accessions of the germplasms suggest that such superior accessions may be useful candidates in genetic breeding programs to improve CG vegetable.